Exploring the Potency of Lower Respiratory Tract Microbiomeas Biomarkers for Lung Cancer - Rasheed, Sama Kamal; Al-Khafaji, Ahmed Salim Kadhim (Iraqi Journal of Science, 2024)
Lung cancer is the first killer among all the known malignancies. Late detection of this malignancy is a major contributor to advanced-stage diagnosis and poor outcomes. Pulmonary microbiota has been recently reported as one of lung cancer risk hallmarks that is still to be fully understood. This study aimed to explore the potential role of microbiome in predicting lung carcinogenesis. Microbiome Library Construction of the 16SrRNA variable region (V3–V4) was conducted by gene amplicon sequencing using the Illumina sequencing platform. Microbiome data was analysed using Version QIIME2-202006 software for species annotations. The sequences were denoised by the DADA2 plugin implemented in QIIMETM2. The bacterial amplicon sequence variants (ASVs) were then identified. The results of 16SrRNA sequencing and gene library bioinformatic analysis indicated that Haemophilus, Prevotella, and Streptococcus were on the top of abundant genera. The species Haemophilus influenza has also been identified among the top 12 bacterial species in malignant and non-malignant lung samples. Microbiome-based identification of the human airway microbiota may provide effective predictive biomarkers for lung carcinogenesis.